2011
DOI: 10.3141/2262-05
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Passing Process on Two-Lane Rural Highways in Spain with New Methodology Based on Video Data

Abstract: Drivers need enough Passing sight distance (PSD) to pass slower vehicles with safety. This can help to improve traffic operation on two-way two-lane highways. Existing models propose different values of PSD, according to different assumptions. Only in some cases these models were based on field data of passing maneuvers.This research proposes the design of a new methodology to observe passing maneuvers on existing highways with help of 6 video cameras installed on a fix point next to passing sections. The use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 7 publications
(15 reference statements)
1
47
0
1
Order By: Relevance
“…Previous research work have collected data of passing maneuver under naturalistic conditions, in order to compare the existing standards with the observed behavior or to analyze other factors involved in the passing process. Recently, some studies have recorded passing maneuvers from external positions (13,14) as well as from instrumented vehicles (15,16). Some of these observations showed that existing design criteria, such as the US previous AASHTO standard could be too conservative.…”
Section: Reliability Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Previous research work have collected data of passing maneuver under naturalistic conditions, in order to compare the existing standards with the observed behavior or to analyze other factors involved in the passing process. Recently, some studies have recorded passing maneuvers from external positions (13,14) as well as from instrumented vehicles (15,16). Some of these observations showed that existing design criteria, such as the US previous AASHTO standard could be too conservative.…”
Section: Reliability Analysismentioning
confidence: 99%
“…Using a combination of video, GPS and laser rangefinder data, following variables were measured ( The length of passing and impeding vehicle Li and Lp were obtained after identifying its brand and model. The selection of the previous variables followed previous research studies (9)(10)(11)(12)(13)(14)(15). These variables provided information about passing duration, passing speeds and distance traveled during passing.…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Levels of service of those highways are increased due to the existence of passing zones, where 4 sufficient passing sight distance is provided. 5 This maneuver is one of the most complex and dangerous on two-lane highways. It involves 6 several decision processes, strongly affected by human factor, road geometry and vehicle 7…”
Section: Alfredo Garcíamentioning
confidence: 99%